SIKAP BAHASA DAN PEMBELAJARAN BAHASA INDONESIA DI PERGURUAN TINGGI - Gusnayetti, Gusnayetti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
A positive attitude is an attitude of enthusiasm towards the use of the language (the language used by the group / speech community where he is). Conversely, if these characteristics have disappeared or weakened from a person or from a group of members of the speech community, it means that a negative attitude towards a language has hit that person or group of people. Law Number 24 of 2009 Article 25 states that Indonesian is a national identity, national pride, a means of unifying various ethnic groups, as well as a means of communication between regions and regional cultures. Therefore, as a user of Indonesian, you should have a sense of pride in using Indonesian. However, in the scope of higher education, a positive attitude towards language is not fully owned by most students. Awareness of loyalty, pride in owning, and maintaining the Indonesian language seems to be lacking. This is because students tend to be more confident when using a foreign language compared to their own language. In the context of learning Indonesian, this task is only borne by Indonesian language teachers and lecturers. This paradigm should be changed because getting used to using Indonesian properly and correctly will reap maximum results in increasing student academic achievement. Understanding Indonesian in accordance with good and correct Indonesian language rules is needed for students to have a positive attitude in using Indonesian. A positive attitude in Indonesian can be shown in the form of language loyalty, language pride, and awareness of language norms.